Cerebral Alterations and Effects of Physical Exercising on the Cognitive enhancement of Alzheimer Disease’s Carriers - Martelli, Anderson (2013)
Alzheimer's disease (AD), is a progressive disturbance of memory and other cognitive functions, becoming the focus of attention and study considering its prevalence increase in the population worldwide.This pathology is characterized by the pathological anathomy finding of the accumulation of senile plaques and neurofibrillary tangles in brain tissue. This review provides a description on AD broaching the major brain alterations and the effects of physical exercising on the cognitive improvement of patients with this pathology. The study was conducted by means of a bibliographical review of its specialized literature, and further consultation of scientific papers in Medline, Scielo, Lilacs and the CAPES Scientific Journals Gateway databases published by 2011 and further consultation of academic books to complement the research besides cross-references of the selected articles. AD is the main manifestation of dementia in the elderly. The appearance of senile plaques and neurofibrillary tangles are only visible histologically in which the latter is considered nowadays the best known neurophysiopathological marker of AD. Studies show that exercising seems to increase cerebral blood flow, stimulating the release of substances that help the CNS functioning with an improvement of the cognitive functions in AD patients which is an important non-pharmacological approach.